Potential of HAB 14 (R3) as an antiepileptic agent / Mohd Syafiq Mod Zin - Mod Zin, Mohd Syafiq (2007)
The aqueous endophyte extract of the root of Cinnamomum zeylanicum (HAB 14(R3)) was prepared and used as 25, 50 and 75 mg/5 ml. 46 white albino mice of both sexes weighing between 30 g and 40 g were used for this study. The results were compared to the negative control and previous study done by other researchers. The extract conferred 100% protection to mice treated with a convulsive dose of picrotoxin, indicating anticonvulsive effect. Thus, the results suggested that the aqueous endopyhte extract of the root of Cinnamomum zeylanicum possesses anticonvulsive properties in mice.